Desain Media Edukasi Interaktif: Flowchart Alur Layanan IT di Rumah Sakit Ibnu Sina YW-UMI Makassar sebagai Sarana Peningkatan Pemahaman - Mangindara, Mangindara; Windarti, Sriyani; Hastuti, Hastuti; Ramadani, Tityn; mawardani, Novya; Utami, Arum Melani Bambang Putri (STIKES Yayasan RS.Dr.Soetomo, 2025)
Effective information technology (IT) services are essential in supporting hospital operations, particularly in ensuring the timely and accurate resolution of technical issues. However, a lack of clear guidance on IT service procedures often hinders staff understanding and response efficiency. This study aimed to design and develop an educational medium in the form of a flowchart to illustrate the IT service procedures at Ibnu Sina Hospital YW–UMI Makassar. The methods used by A descriptive qualitative approach was employed using a Problem-Based Learning (PBL) method. Data collection techniques included semi-structured interviews, field observations, and document analysis. The Results are the developed educational medium, in the form of a flowchart, systematically illustrated the IT service workflow through several stages: interviews with the IT unit, field observations and document review, drafting the service flow, validation with stakeholders, visual design using graphic software, and presentation and dissemination to users. The flowchart effectively improved staff understanding, accelerated service response, and reduced procedural errors. The flowchart served as a practical and user-friendly educational medium that enhanced the clarity and efficiency of IT services. Its implementation is expected to contribute to faster problem resolution and support improved healthcare service quality within the hospital.